We have to prove that cos 4x - sin 4x * cot 2x = -1

cos 4x - sin 4x * cot 2x = -1

use cos 2x = (cos x)^2 - (sin x)^2 and sin 2x = 2 sin x cos x and cot x = (cos x)/(sin x)

=> (cos 2x)^2 - (sin x)^2 - 2*(sin 2x)*(cos 2x)*(cos 2x)/(sin 2x)

=>(cos 2x)^2 - (sin x)^2 - 2*(cos 2x)*(cos 2x)

=> ( cos 2x)^2 - 2 ( cos 2x)^2 - ( sin 2x)^2

=> - (cos 2x)^2 - (sin 2x)^2

=> -1*[(cos 2x)^2 + (sin 2x)^2]

As (cos x)^2 + (sin x)^2 = 1

=> -1

Therefore we proved that

**cos 4x - sin 4x * cot 2x = -1**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.